TANNASE ACTIVITY AS A CRITERION FOR THE SELECTION OF PROBIOTIC MICROORGANISMS - Starovoitova , S.A. (Eurasian Journal of Applied Biotechnology, 2016)
Types of tannins and their sources for selection, and characteristics such as the structure and properties of the tannins, especially those of bacterial origin, were considered. The positive and negative properties of various tannins, mainly those of vegetable origin, were reviewed. The methods of biodegradation of the main types of tannins and enzymes involved in the processes of their decomposition were analysed. The possibility of using tannins and their properties in various industries, especiallyin food and pharmaceutical industries, was discussed. The data of many known researchers with respect to bacterial tannase activity and methods of determination and isolation of bacteria with tannase activity were summarized. The main tannase-producing bacteria, especially those with potential probiotic properties and use in creating bacterial drugs and functional foods (namely, bacteria that belong to the genera such asLactobacillus, Bacillus, Enterococcus,andPentococcus), were shown. Application perspectives of the tannase activity of probiotic microorganisms as a basis for pharmaceutical products-probiotics and functional foods enriched with probiotic microorganisms that have relevant antioxidant and anti-tumour properties—were discussed. The practical uses of tannase are still quite limited because of insufficient information on its properties and the complexity of its production and purification.